Forensic Experts′ Opinion Regarding Clinical Forensic Medicine Practice in Indonesia and Malaysia - Hanusha Nair Gopalakrishnan; Yoni Fuadah Syukriani; Elsa Pudji Setiawati (Journal of Forensic Science and Medicine, 2016)
Clinical forensic medicine is a progressing branch. In Indonesia and Malaysia, there is inadequate information regarding this practice. It is always unclear about the job scopes and practitioners involved in this field. The study outlined in this article is aimed to explore the current clinical forensic medicine practice compared to existing systematic practice globally and hence analyzing for presence of difference in this practice between these two countries. A qualitative study was conducted by forensic experts in Indonesia and Malaysia from September to November 2015. In-depth interview was carried out to obtain data which were then validated using literature and legal documents in Indonesia and Malaysia known as the triangulation validation method. Data were presented in narrative form. In Indonesia, forensic pathology and clinical forensic medicine were approached as one whereas in Malaysia separately. This practice was conducted by a general practitioner in collaboration with other specialists if needed in Indonesia; whereas, in Malaysia, this practice was conducted by forensic pathologists or medical officers in the absence of forensic pathologists. Both Indonesia and Malaysia followed the continental regimen in practicing clinical forensic medicine. There was still a lack of involvement of doctors in this field due to lack of understanding of clinical forensic medicine. The current clinical forensic medicine practice has not developed much and has no much difference in both countries. The gap between the current practice with systematic practice cannot be justified due to the absence of one standardized code of practice.